Introduction of Mobile Health Tools to Support COVID-19 Training and Surveillance in Ogun State Nigeria - Otu, Akaninyene; Okuzu, Okey; Ebenso, Bassey; Effa, Emmanuel; Nihalani, Nrip; Olayinka, Adebola; Yaya, Sanni (Frontiers in Sustainable Cities, 2021)
Mobile health (mhealth) tools delivered through wireless technology are emerging as effective strategies for delivering quality training, ensuring rapid clinical decision making and monitoring implementation of simple and effective interventions in under-resourced settings. We share our early experience of development and deployment of the InStrat COVID-19 health worker training application (App) in Ogun state, Western Nigeria where the country’s first case was reported. This App was designed to directly provide frontline health workers with accurate and up-to-date information about COVID-19; enable them to quickly identify, screen and manage COVID-19 suspects; provide guidance on specimen collection techniques and safety measures to observe within wards and quarantine centres dealing with COVID-19. The App was deployed in 271 primary health care facilities in Ogun State and a total of 311 health workers were trained. Of the 123 health workers who completed knowledge pre- and post-tests, their average test score improved from 47.5(±9.4) % to 73.1(±10.0) %, P < 0.0001 after using the tutorial. Rapid adoption and uptake were driven largely by public-private sector involvement as well as certification with reported satisfaction levels of over 95%. Challenges encountered included a lack of universal availability of android phones for frontline health workers, lack of internet access in remote areas and a need to incentivize the workers. The timely deployment of this App targeting primary health care workers, mostly in hard-to-reach areas, obviated the need for conventional didactic training with potential of savings in training costs and time and could be applied to similar contexts.